Estudio financiero de riesgo y rendimiento de las inversiones de las COACs de segmento dos hacia las COACs de segmento uno que forman parte de Red Equinoccio - Donoso Luna, Isabel Cristina (2015)
The Organisms of Popular and Solidarity Economy have increasingly developed in recent years and its market participation has been increasing. This has happened due the emphasis that the national government has done to achieve its objectives and strategic goals, through the creation and strengthening of the Superintendence of these organisms. Nowadays, there is no much information that have been conducted to analyze to this important organism, therefore is necessary to make a Financial Risk Analysis and Performance Investment Study of the Savings and Credit Cooperatives of segment two to the savings cooperatives of the segment one, which belong to Red Equinoccio to determine the current causes and the present needs of the entity of segment two and the cooperative of the segment one compared to the present needs and investment respectively. In the cooperative sector with have a large amounts of investments that are not generating higher returns for credit unions. Despite being laid down in the Law of Popular and Solidarity Economy that investments should be made in the first instance unions credit, it is not doing because of the uncertainty generated by not providing the tools to analyze profoundly the credit unions segment one that are the greatest need over the accounts. The best investment decisions to generate returns that comply investor expectations, it is necessary to generate a model of investment that guarantees the return on investment, that this level of uncertainty can be mitigated.